2020
DOI: 10.1039/c9ra08680c
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of multifaceted lactoferrin or graphene oxide functionalized silver nanocomposites biosynthesized using mushroom waste and chitosan

Abstract: Biosynthesis of multifaceted silver nanoparticles using waste mushroom and chitosan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 67 publications
0
30
0
Order By: Relevance
“…AgNPs also have strong affinity towards the sulfur-containing proteins in the microbial cell wall. The attachment of AgNPs towards the membrane of microbes causes irreversible morphological changes in the structure of cell membrane [65]. This can also cause a loss in the integrity of lipid bilayer and the permeability of the cell membrane.…”
Section: Antibacterial Properties Of Agnpsmentioning
confidence: 99%
“…AgNPs also have strong affinity towards the sulfur-containing proteins in the microbial cell wall. The attachment of AgNPs towards the membrane of microbes causes irreversible morphological changes in the structure of cell membrane [65]. This can also cause a loss in the integrity of lipid bilayer and the permeability of the cell membrane.…”
Section: Antibacterial Properties Of Agnpsmentioning
confidence: 99%
“…The combination of Ag and GO is also proved to reduce the agglomeration of Ag NPs. GO is a two-dimensional material made up of a single hexagonally arranged layer of sp 2 -bonded carbon atoms with large surface areas and numerous oxygen-containing functional groups such as hydroxyl, epoxy, and carbonyl groups protruding from GO backbones, which make the GO more hydrophilic [ 165 , 166 ]. Thus, it offers excellent dispersion of NPs on the edges of its planes through chemical bonding even at high concentrations.…”
Section: Nanotechnology-based Antimicrobial Applicationsmentioning
confidence: 99%
“…Xiang et al proposed a method to boost the antimicrobial action of titanium (Ti) implants through coating with poly(lactic-co-glycolic acid)/ZnO nanorods/Ag NPs and their results revealed that the cytotoxicity of PLGA-ZnO-AgNPs was lower than ZnO and ZnO-Ti against mouse preosteoblasts (MC3T3- E1) cells [ 166 ]. In another study, Ti alloy (Ti6Al4V) dental implants were coated with Ag NPs, together with hydroxyapatite (HA) and 3 samples were prepared: Ti6Al4V with Ag NPs, Ag NPs plus HA microparticles (Ag+mHA), or Ag NPs plus HA NPs (Ag+nHA) [ 157 ].…”
Section: Biocompatibility Of Nanoparticlesmentioning
confidence: 99%
“…5 Recently, LTF has been attached onto the surface of biosynthesized AgNPs by which reduction of silver ions to AgNPs was achieved using a spent mushroom substrate (SMS, a mushroom waste after harvesting). 6 The resulting Ag-LTF was also capped with chitosan for nanoparticle stabilization and biocompatibility enhancement. In this study, Ag-LTF had higher antibacterial activity against selected bacterial strains as than their single components.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, Ag-LTF had higher antibacterial activity against selected bacterial strains as than their single components. 6 This has led to the development of a carrier for Ag-LTF, to be used as a dressing for infected wound treatment.…”
Section: Introductionmentioning
confidence: 99%